Necrotizing leukoencephalitis in a Yorkshire dog from Brazil - Amude, Alexandre Mendes; Arias, Mônica Vicky Bahr; Headley, Selwyn Arlington; Bracarense, Ana Paula Frederico Rodrigues Loureiro; Silva, Natalino Francisco; Alfieri, Amauri Alcindo (Semina: Ciências Agrárias, 2019)
Necrotizing leukoencephalitis (NLE) is an uncommon inflammatory condition of brain of dogs, and was described in dogs from North America, Europe, and Asia. Cases of NLE from South America were not located when major data bases were examined. Consequently, this report describes the findings associated with NLE in a Brazilian 3.5-year-old female Yorkshire dog with neurological findings related to the myelencephalon; the dog died, besides medical treatment, and was submitted for autopsy exam and histopathological evaluation. Lesions were restricted to the encephalon and characterized as leukoencephalomalacia with severe non-suppurative inflammation with extensive perivascular cuffing; the non-suppurative inflammation was characterized by influx of lymphocytes and histiocytes, and occasionally plasma cells, and gitter cells. Infectious disease agents were not identified by molecular techniques or visualized with histochemical stains. This report represents the first definitive diagnose of NLE in Brazil, suggesting that this disease may be present in South America dogs suffering from neurological conditions. This knowledge may be useful for veterinarians in Brazil, taking into account that this disease should be considered as a differential diagnosis when infectious causes are excluded.